Religious Moderation, Five Loves, and National Values in Islamic Religious Education Learning - Alim Bakhri; Dika Tripitasari; Muhdin Muhdin (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to reconstruct the integration of religious moderation, Panca Cinta (Love), and national values ​​in Islamic Religious Education (PAI) learning. The background of this study is based on the still partial approach to PAI learning that tends to separate the spiritual, social, and national dimensions. This study uses a qualitative approach with library research, which analyzes various primary and secondary sources related to religious moderation, the concept of mahabbah in Islam, and national values ​​in the Indonesian context. The results show that religious moderation functions as an epistemological framework, Panca Cinta as an ontological-axiological foundation, and national values ​​as an orientation for social praxis. These three concepts have an interdependent relationship that can be constructed in an integrative learning model based on ontology-epistemology-axiology. This model produces transformative, inclusive, and contextual PAI learning, and is able to shape the religious-national character of students. This study provides a theoretical contribution to the development of PAI learning designs based on value integration that is relevant to the challenges of the plurality of Indonesian society.